PEMBUATAN ALAT MISTAR PADA OLAHRAGA LOMPAT TINGGI MENGGUNAKAN PANEL SURYA BERBASIS IOT - Mutttaqin, Nashrul; Howenoki, Alfonso; Sulistyo, Eko; Vina Ratnaputri, Valentin (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
High Jump is one of the most popular sports in the world. The ruler is the main measuring tool in this sport, but until now the height of the ruler is still manually adjusted. This study aims to design and create a high jump ruler that uses solar energy and is based on the Internet of Things (IoT). This tool is designed to help high jump athletes measure jump heights more accurately and efficiently. This system uses a NodeMCU ESP32 microcontroller and ultrasonic sensors to detect the position of the ruler, real-time data, whether or not the athlete is successful in jumping, then the data is sent to the IoT server to be processed and displayed in the form of real-time data. Solar energy is used as a power source to drive this system, so that this tool can be used in the field without the need for additional electricity. The results of the study show that this IoT-based high jump ruler can measure jump height with high accuracy and can be used as a training/tournament aid for high jump athletes.